The grading effect of coarse sand on consolidated undrained strength behaviour of sand matrix soils - Othman, Bakhtiar Affandy; Marto, Aminaton; Mohd Yunus, Nor Zurairahetty; Tan, Choy Soon; Pakir, Faizal (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In geotechnical engineering field, the behaviour of soil does rely much on the shear strength for design purpose. Previously, findings show that the change of grained size in soil will change the structure (microstructure) and behaviour of the soil; consequently, affected the strength. To date, limited study focused on the effect of grading on the behaviour of sand fine mixtures. This study aims to investigate the effect of coarse sand on undrained strength behaviour of sand matrix soils in comparison with clean sand. A series of test on reconstituted sand matrix soils had been carried out by conducting consolidated undrained (CU) triaxial test using GDS ELDYN® triaxial machine. Coarse sand (retain within 2.0 mm to 0.6 mm) was mixed with 0%, 10 %, 20%, 30%, and 40% of fine particles (kaolin) independently by weight to prepare reconstituted samples. Triaxial samples of 50 mm diameter and 100 mm height were prepared using wet tamping technique (5% of moisture content) with targeted relative density at 15% (loose state). Each reconstituted sample was sheared at two effective confining pressures of 100 kPa and 200 kPa, respectively. Results show that the gradation contributed to the behaviour of the sand matrix soils. Increasing percentage of coarse sand in sand matrix soils exhibited higher effective friction angle. Similar trends were also observed on the angularity effect on undrained shear strength parameters.